Respuesta :
Answer:
Subtract each term from the polynomial until you find the matching polynomial.
Step-by-step explanation:
Subtracting each answer option below yields the following polynomials:
A) [tex]y^2-5y+1-0= y^2-5y+1[/tex]
B) [tex]y^2-5y+1-5 = y^2-5y-4[/tex]
C) [tex]y^2-5y+1-y^2 = -5y+1[/tex]
D) [tex]y^2-5y+1 - (4y^2-y+7) \\y^2 -5y+1-4y^2+y-7\\-3y^2-4y-6[/tex]
Answer:
A) y² - 5y + 1
B) y² - 5y - 4
C) - 5y + 1
D) - 3y² - 4y - 6
Step-by-step explanation:
Let's call P the unkown polynomial and D the difference. In each case, the following must be true:
y² - 5y + 1 - P = D
A)
y² - 5y + 1 - P = 0
y² - 5y + 1 = P
B)
y² - 5y + 1 - P = 5
y² - 5y + 1 - 5 = P
y² - 5y - 4 = P
C)
y² - 5y + 1 - P = y²
y² - 5y + 1 - y² = P
- 5y + 1 = P
D)
y² - 5y + 1 - P = 4y² - y + 7
y² - 5y + 1 - 4y² + y - 7 = P
- 3y² - 4y - 6 = P